Study of hTERT and Histone 3 Mutations in Medulloblastoma - Pereira, Marta Sofia Carvalho Ribeiro Viana (2017)
CNPq/Universal (475358/2011-2), Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP; 2012/19590-0) and Fundação para a Ciência e Tecnologia (FCT; PTDC/SAU-ONC/115513/2009) grants to R.M.R. The project was cofinanced by Programa Operacional Regional do Norte (ON.2-O Novo Norte), Quadro de Referência Estratégico Nacional (QREN) and Fundo Europeu de Desenvol- vimento Regional (FEDER). M.V.-P. is the recipient of an FCT Post-Doctorate Research Fellowship (SFRH/BPD/104290/2014)